High pesticide exposure events and DNA methylation among pesticide applicators in the agricultural health study. (20th December 2016) - Rusiecki, Jennifer A.; Beane Freeman, Laura E.; Bonner, Matthew R.; Alexander, Melannie; Chen, Ligong; Andreotti, Gabriella; Barry, Kathryn H.; Moore, Lee E.; Byun, Hyang‐Min; Kamel, Freya; Alavanja, Michael; Hoppin, Jane A.; et al.
Abstract : Pesticide exposure has been associated with acute and chronic adverse health effects. DNA methylation (DNAm) may mediate these effects. We evaluated the association between experiencing unusually high pesticide exposure events (HPEEs) and DNAm among pesticide applicators in the Agricultural Health Study (AHS), a prospective study of applicators from Iowa and North Carolina. DNA was extracted from whole blood from male AHS pesticide applicators ( n = 695). Questionnaire data were used to ascertain the occurrence of HPEEs over the participant's lifetime. Pyrosequencing was used to quantify DNAm in CDH1, GSTp1, and MGMT promoters, and in the repetitive element, LINE‐1 . Linear and robust regression analyses evaluated adjusted associations between HPEE and DNAm. Ever having an HPEE ( n = 142; 24%) was associated with elevated DNAm in the GSTp1 promoter at CpG7 (chr11:67, 351, 134; P < 0.01) and for the mean across the CpGs measured in the GSTp1 promoter ( P < 0.01). In stratified analyses, elevated GSTP1 promoter DNAm associated with HPEE was more pronounced among applicators >59 years and those with plasma folate levels ≤16.56 ng/mL (p‐interaction <0.01); HPEE was associated with reduced MGMT promoter DNAm at CpG2 (chr10:131, 265, 803; P = 0.03), CpG3 (chr10:131, 265, 810; P = 0.05), and the mean across CpGs measured in the MGMT promoter ( P = 0.03) among applicators >59 years and reduced LINE‐1 DNAm ( P = 0.05) among applicators with ≤16.56 ng/mL plasma folate. Non‐specific HPEEs may contribute to increased DNAm in GSTp1, and in some groups, reduced DNAm in MGMT and LINE‐1 . The impacts of these alterations on disease development are unclear, but elevated GSTp1 promoter DNAm and subsequent gene inactivation has been consistently associated with prostate cancer. Environ. Mol. Mutagen. 58:19–29, 2017. © 2016 Wiley Periodicals, Inc.